Assessment Of Determinants Of Islamic Cooperatives's Patronage In Nigeria, A Case Study Of Albirr Islamic Cooperative - Abdulkabir Olaitan (al-Afkar, Journal For Islamic Studies, 2023)
This paper aims to assess the determinants of patronage for Islamic cooperatives in Nigeria, with a specific focus on Albirr Islamic Cooperative. The study employs a mixed-methods approach, including both quantitative data analysis and qualitative interviews with members of Albirr. The findings suggest that factors such as trust, social ties, religious affiliation, and economic benefits all contribute to the decision to patronize Islamic cooperatives. Additionally, the study highlights the importance of effective management and communication in maintaining and growing membership for Islamic cooperatives. The paper concludes that a deeper understanding of these determinants can inform strategies for increasing the success and impact of Islamic cooperatives in Nigeria and other similar contexts.